Usulan Kebijakan Persediaan Perangkat Network Terminal Equipment (NTE) Menggunakan Metode Continous Review (s,S) untuk Meminimasi Biaya Persediaan pada PT XYZ - Syafa Mediana Azzahra; Novitasari, Nia; Sumargo, Seto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
PT XYZ is a company who operates in the technology services, information, and communication technology as well as telecommunications networks that have digital services providing internet, home telephone and TV. PT XYZ uses a device called Network Terminal Equipment (NTE). In an effort to maximize the range of services provided, this company has seven warehouses spread throughout Indonesia. Where each regional warehouse must be supported by a good inventory process to optimize equipment and minimize inventory costs. However, in actual conditions PT XYZ experienced several problems in the supply of NTE equipment, one of which was overstock. Therefore, this research was conducted to determine the optimal inventory policy in each PT XYZ regional warehouse in order to reduce overstock and minimize inventory costs. The method used in this research is Continuous Review (s, S) which can help determine order lot size, safety stock, and reorder point. Based on the proposed inventory policy calculation using Continous Review (s,S) method PT XYZ can reduce the total inventory cost about 87% or Rp410,585,661.67 in a year for each warehouse.